Are workers on board vessels involved with chemicals from treated ballast water sufficiently protected? – A decadal perspective and risk assessment. (May 2020) - Dock, Annette; Linders, Jan; David, Matej; Gollasch, Stephan; David, Jan; Ziegler, Gregory
Abstract: Ballast Water Managements Systems (BWMS) installed on vessels may use Active Substances (AS) to inactivate organisms. This paper provides new insights in the global issue of noxious Disinfection By-Products (DBP) produced with primarily oxidant-based BWMS, and the risk assessment for workers, including port State control officers, while performing tasks on a vessel that involve exposure to treated ballast water. The Joint Group of Experts on the Scientific Aspects of Marine Environmental Protection – Ballast Water Working Group (GESAMP-BWWG) plays a role in the certification process of BWMS that make use of AS evaluating potential negative effects. All BWMS that passed GESAMP-BWWG Final Approval until mid 2019 were analyzed providing an overview of chemicals in the treated ballast water before and after neutralization. The ballast tank cleaning scenario, the sampling scenario, and the ballast tank inspection scenario all showed elevated human health risks using the Derived Minimal Effect Levels approach. The most critical exposure occurs in the ballast tank cleaning scenario through the inhalation of volatile DBP, such as tribromomethane. This substance may cause acute effects such as headache, dizziness and also has carcinogenic properties. The two risk reducing options available in the GESAMP-BWWG Tier 2 calculations were compared, one being mitigation measures such as protective gloves and coveralls, the other option is taking into account a time correction factor. The results showed that the trihalomethanes in air are most problematic, however, there is a possibility that the calculated values may be overestimated as generally worst case assumptions were used. Highlights: Concentrations of chemicals generated by 45 BWMS were studied. Active substances, DBP and neutralizers were analyzed. Different DBP exposure routes were compared. Human health risk caused by treated ballast water was noted for on board workers. Potential overestimation during inhalation of trihalomethanes was identified.